STUDY ON NONLINEAR VIBRATION CHARACTERISTICS FOR THE ROTOR-ROLLING BEARING SYSTEM WITH CURVIC COUPLINGS (MT) - WANG LongKai; MA PengWei; WANG AiLun; ZHANG HaiBiao; YIN YiJun (Jixie qiangdu)
To study the contact effect of the rotor system with curvic couplings under rolling bearing supports, the combination of 3D finite element and analytical method were used to derive the curvic coupling shaft section stiffness matrix, and the dynamics model of rotor-rolling bearing system was established, which was verified by Ansys. By comparing with the continuous rotor, it was found that the curvic coupling structure reduced the first-order critical rotor speed by 5% and increased the amplitude by 3%. The results show that the nonlinear bifurcation trend of the curvic coupling rotor is nearly the same as that of the continuous rotor, however, the discontinuous characteristic of the curvic coupling structure will make the rotor access or leave the periodic motion state significantly earlier. Obviously, the contact effect needs to be considered when analyzing the rotor vibration characteristics with curvic couplings. The research can provide analysis methods and design ideas for the prediction of nonlinear vibration characteristics and the operating speed design for rotor system with curvic coupling structure.